SISTEM INFORMASI UMKM KAMPUNG GERABAH DESA PAGELARAN BERBASIS ANDROID - Mohammad Nur Ali Furqon; Chaulina Alfianti Oktavia (Universitas Teknokrat Indonesia, 2022)
The development of information and communication technology marked by the internet has brought society into a new era. Information and communication technology can solve problems and reduce the burden on SMEs. On the other hand, based on data from the MSME organization of the Pottery Village, Pagelaran Village which consists of 25 pottery craftsmen and there are 24 pottery craftsmen who do not have a desktop or laptop computer, 22 of all craftsmen use mobile phones based on the Android operating system. For the method of data collection is done by means of interviews, literature studies and observation. Utilization of IT can be done by MSME actors to provide complete information about products, manufacturing locations, product descriptions, and features for ordering MSME products that can be used as a means to promote and introduce MSME centers in the Pagelaran Village. With the application of the MSME information system, Kampung Gerabah now has media for promotion and marketing of handicraft products and it is hoped that it can help improve the economy of the residents of the pottery village of Pagelaran Village. This application was successfully built using the Java programming language and PHP as an android application builder. The Codeigniter and Android Native frameworks are used to display product catalogs, craftsman information, customer information, so that it can make it easier for application users to get information. In this application, the Raja Ongkir API is used to calculate the cost of product delivery costs. As for the navigation features in this application using the Google Maps API. suggestions for further application development, namely in terms of presenting information to users and developing new features that can improve the application.